2020
DOI: 10.21203/rs.2.14045/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress, stressors and related factors in clinical learning of midwifery students in Iran: a cross sectional study

Abstract: Background: Midwifery is an emotionally challenging profession, and academic education of midwifery especially clinical learning has its own specific challenges. Midwifery students face with stressful experiences, especially related to instructor and characteristics of clinical environment, which can affect their theoretical and practical abilities. There is insufficient evidence in this field. This study aimed to explore (1) the perceived stress and stressors of midwifery students and (2) the relationships be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In the current study, 10% of students had severe stress. A previous study reported that 9% of nursing students hah high-stress levels, mainly due to social, financial, and academic factors (Rezaei et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, 10% of students had severe stress. A previous study reported that 9% of nursing students hah high-stress levels, mainly due to social, financial, and academic factors (Rezaei et al, 2020).…”
Section: Discussionmentioning
confidence: 99%